Testing as one of the innovative methods of organizing training and control at the lesson of the Russian language and literature - Mirzayunusova Z.I., (Zien Journals, 2022)
In the modern learning process, non-traditional (innovative) for domestic education methods, forms, means of training and control have become widespread. These include tests. The system of test tasks, have a specific organization and are created in order to identify the special abilities of students; measuring the level of knowledge; evaluation of the results achieved by them in the learning process. The test as a form of control allows all students to work simultaneously in the same conditions and record the performance with symbols.
Keywords: methods; forms; tasks